Influence of standing position on mechanical and energy costs in uphill cycling - Bouillod, A.; Pinot, J.; Valade, A.; Cassirame, J.; Soto-Romero, G.; Grappe, F. (Journal of Biomechanics, 2018)
This study was designed to examine the influence of standing position (vs. seated) during uphill cycling on both mechanical cost (MC) and energy cost (EC) in elite cyclists. For the study, thirteen elite cyclists (VO2max: 71.4 ± 8.0 ml·min-1·kg-1) performed, in a randomised order, three sets of exercises. Each set comprised 2 min of exercise, alternating every 30 s between seated and standing postures, using different slopes and intensity levels on a motorised treadmill. MC was calculated from the measurement of power output and speed, whereas EC was calculated from the measurement of oxygen consumption and speed. MC was significantly higher (+4.3%, p < 0.001) in standing position compared to seated position when all slopes and intensities were considered. However, EC was not significantly affected by the change in position. The standing position also induced a significant increase in rolling resistance power (p < 0.001), rolling resistance coefficient (p < 0.001) and lateral sways (p < 0.001). The significant increase in MC observed in standing position was due to a higher rolling resistance induced by bicycle sways and a shift forward of the centre of mass compared to seated position. This result should lead bicycle tire manufacturers to reduce the increase in rolling resistance between the two positions. Considering the relationship observed between the MC and bicycle sways, cyclists would be well advised to decrease the bicycle sways in order to reduce the MC of locomotion.